PEMATUHAN PRINSIP KERJASAMA ANTARA PELAKU PERCAKAPAN PADA NOVEL BERJUDUL “HARRY POTTER DAN BATU BERTUAH” - Ida Ayu Panuntun (LPPM Universitas Pekalongan, 2013)
Cooperative Principle is a principle which used to become an effective communication. It often appears in the conversation. Cooperative Principle was proposed by Grice in 1975. It consists of four maxims in the conversation. Those are quantity maxim, quality maxim, relevance maxim and manner maxim. The observance of the four maxims used in order to gain the meaningful conversation. Novel entitled “Harry Potter dan Batu Bertuah” is one of the most popular novels. The conversations among the characters in that novel is interesting to be analyzed. The purposes of the study are to identify the maxims which observe the cooperative principle in term of meanings. The method used in this study was descriptive qualitative with cooperative principle analysis approach. The objects of the study were 43 conversations. To analyze the conversations which observe the maxims are done by interpreting the meanings of the conversation. The findings of the conversations which observe the cooperative principle are as follow: 60.5% utterances observe the maxim of quantity; 16.3% utterances observe the maxim of relevance; 16.3% utterances observe the maxim of manner and 7% utterances observe the maxim of quality. The finding is also suggested as a recommendation in the teaching learning process for the advanced learner level and the senior high school level. This findings can be applied in the advanced learner level in transferring the material of speaking. Another recommendation is suggested for the senior high school level in the English subject. It can be applied in the discussion of the material and question and answer session between the teacher and the students.Keywords: speech act, conversation, cooperative principle